Dampak Mindset Bertumbuh (Growth Mindset) terhadap Motivasi Intrinsik dan Ketahanan Akademik Siswa - Abdi Cahya Subekti; Akbar Nor Rochmat; Ma’mun Hanif (Yayasan Al-Afif, 2025)
Students’ beliefs about their intellectual abilities play a crucial role in shaping the quality of their learning experiences. The belief that abilities are fixed often leads students to give up easily when facing failure, which in turn reduces intrinsic motivation and academic resilience. This article aims to comprehensively examine the relationship between growth mindset, intrinsic motivation, and academic resilience within the context of Indonesian education. The study employs a descriptive qualitative approach through a literature review of academic books, national and international journal articles, and relevant research reports published over the past ten years. A thematic analysis is used to synthesize key findings and construct an integrated conceptual understanding. The results indicate that a growth mindset serves as a psychological foundation that encourages students to perceive challenges and failures as natural parts of the learning process. This mindset is closely associated with higher levels of intrinsic motivation, more adaptive emotional regulation, and a stronger capacity to persist and recover from academic difficulties. Furthermore, the interaction between growth mindset and intrinsic motivation forms a positive cycle that continuously strengthens students’ academic resilience. These findings highlight the importance of educational interventions that go beyond a sole focus on academic outcomes and instead prioritize the development of students’ mindsets, autonomy, and psychological resilience in school settings.